On Terminology and its Role in the Science of Language - Ghumashyan, Varduhi (Armenian Folia Anglistika, 2008)
Terminology is an integral part of any branch of science. Refined terminology proves to be the efficient means to ensure the development of the given branch.It is common knowledge that lexicology is a special branch since it deals with the idea of the conventional sign system rather than the “ordinary language”. Evidently, terms are the words and word combinations which convey extralinguistic notions and categories. There are numerous and various definitions of terms dependent on the peculiarities of the given branch of science.The use of terms and terminological phrases gets more important in the context of the rapid development observed in diverse branches of science in recent years when scientific communication has obtained a wider scope.